Strategic Leadership and Organizational Performance: A Critical Review of Literature - Jaleha, Alex A.; Machuki, Vincent N. (European Scientific Journal, ESJ, 2018)
Effective strategic leadership is considered as a major ingredient for the successful performance of any organization operating in the ever dynamic and complex environment of the 21st century. In the context of information uncertainty and resource scarcity, strategic leadership is required to confront the reality of environmental turbulence and a continuous need for appropriate organizational change in order to achieve performance goals. Most of the conceptual and empirical studies have shown that strategic leadership actions significantly influence performance. Despite its importance, studies have demonstrated that the influence of strategic leadership on organizational performance is contingent upon situational constraints or random effects. To date, very little empirical research has analyzed the direct and indirect relationship between strategic leadership, external environment, organizational change and performance. This paper seeks to unearth this research gap by critically reviewing relevant conceptual and empirical literature to bring out the possibility that the external environment and organizational change could influence the relationship between strategic leadership and organizational performance. The paper advances the emerging postulations which anchor a conclusion that the direct effect of strategic leadership on performance is contested and hence inconclusive due to possible moderating and mediating influence of the external environment and organizational change respectively. It is hoped that the paper’s postulations would guide empirical research in various contexts to hasten addressing of the extant knowledge gaps.